Czynniki ograniczające udział polskiej gospodarki w korzyściach płynących z globalizacji - Gasz, Małgorzata (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
Globalization processes have influenced the structure and the way of national economy functioning. There are different tendencies and functions of the above processes in particular markets. Benefits based on globalization especially depend on the factors of national markets' activity, ability of making particular costs and undertaken methodological solutions. Though different countries are beneficiaries on different levels. The subject of this thesis is an analysis of potential benefits for Polish economy in globalization process and an attempt to localize "bad influence factors" in achieving those benefits. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 112-118